Head-Neck Taper Corrosion following Total Hip Arthroplasty with Stryker Meridian Stem. Issue 6 (10th November 2016) - Patel, Sonika; Talmo, Carl T.; Nandi, Sumon
Background: Taper corrosion at the modular junctions of total hip arthroplasty (THA) femoral stems are known to cause locally destructive adverse local tissue reaction (ALTR). However, the implants at risk remain to be fully elucidated. Case review: We report the case of a 76-year-old woman with hip pain, abductor weakness, and sciatic nerve symptoms 2 years following metal-on-polyethylene THA. Serum cobalt levels were elevated, while chromium levels were normal. Magnetic resonance imaging demonstrated ALTR. The patient's symptoms resolved following head and liner exchange with ceramic head and titanium sleeve. Literature review: Previous studies have reported ALTR secondary to head-neck taper corrosion in cobalt chrome alloy and titanium alloy stems used in metal-on-polyethylene (MoP) THA. The stems described above span 4 manufacturers with varying taper geometries. To our knowledge, this is the first report of ALTR due to head-neck taper corrosion in a Stryker Meridian titanium-molybdenum-zirconium-iron (TMZF) alloy stem. Clinical relevance: Close surveillance for ALTR may be considered in patients with this prosthesis. Further investigation of the TMZF alloy and V40 taper geometry of this stem may guide future implant design.